PENGARUH CITRA MEREK TERHADAP MINAT BELI PRODUK HALAL NETWORK INTERNASIONAL (HNI) DI KOTA BAUBAU - Nurrahmawati Alitasi, Wa Ode; Hasni (Journal Economics Technology And Entrepreneur, 2024)
This study aims to determine whether brand image affects the intention to buy Halal Network International (HNI) products in Baubau City. The type of research used in this study is a type of quantitative research. The population of this study is the people of Baubau city who have purchased HNI products. Sampling using the Slovin formula, the number of samples in this study amounted to 93 respondents. The validity test uses the product moment correlation technique and the reliability test uses the Cronvach Alpha formula. Based on the results of the regression analysis, this can be seen from the results of the hypothesis test, the influence of this brand image is positively significant with a sig value of 0.000 meaning that if the brand image is better, it will increasingly generate or encourage buying interest. Based on the results of the determinant coefficient, the adjust R Square is 0.532. The result of this statistical calculation means that the ability of the independent variable to explain the variation in the dependent variable is 53.2%, and the rest is influenced by other factors which are not examined further in this study. From this research it can be concluded that brand image has a positive effect on purchase intention.